Improved agro-technique for makhana cultivation - Kumari, Priyanka; Kumar, Amrendra; Kumar, Anjani; Bhadauria, Pragya; Kumari, Pushpa (Indian Farming, 2024)
Makhana is mainly cultivated in North Bihar, mainly Seemanchal area. It has good health benefits, many medicinal values and most common dry fruit which has low or negligible fat content, but rich in protein, carbohydrates and minerals. It is used for milk-based food preparations like kheer, pudding etc. To enhance its economic significance, standard agro-techniques such as improved varieties (viz. Sabour Makhana 1, Swarna Vaidehi), climate and cultivating system, integrated nutrient management (INM), harvesting techniques, and post-harvest packages are necessary to the farmers in order to realize potential yield and achieve better returns. The yield of improved varieties ranges from 28-30 q/ha and pop recovery from 50-55%.